ISLAM AND DEMOCRACY: THE POLITICAL THOUGHT OF B.J. HABIBIE - Rahmadani, Gema (Program Pascasarjana UIN Sumatera Utara Medan, 2024)
Research This study examines B.J. Habibie's political thought regarding the relationship between Islam and democracy, focusing on how the two can strengthen each other in the Indonesian context. Indonesian context. Using a literature study approach and qualitative analysis approach and qualitative analysis, this research explores Habibie's argument that principles of principles of democracy, such as social justice, deliberation, and freedom of speech, are in line with Islamic teachings. In addition, it identifies challenges faced in the integration of these values, including radicalization and identity politics. Through text analysis and interviews with experts, this research shows that Habibie's thought offers an optimistic an optimistic perspective regarding the implementation of democracy in a country with a large Muslim population. Muslim population. The findings show that education and interfaith dialog are key are key in overcoming challenges and realizing harmony between Islam and democracy. and democracy. This research is expected to contribute to a deeper understanding of the potential synergies between religious values and democratic practices, as well as their relevance to political development in and democratic practices, and their relevance for political development in Indonesia. Indonesia